2013
DOI: 10.1111/icad.12032
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in the composition of aphidophagous coccinellid communities in Central Europe

Abstract: 1. Coccinellids (Coleoptera: Coccinellidae) provide important ecosystem services as biocontrol agents in contributing to the regulation of key agricultural pests. It is generally accepted that biodiversity of native coccinellid communities has been declining during recent decades. Here, we present the results of a long-term study of coccinellid communities and report an attempt to determine whether recent changes in land use have affected their composition.2. Coccinellids were sampled in cereal crops, on wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…There are very few published long‐term studies of ladybird communities in Europe, and even fewer that have encompassed the early invasion phase of a non‐native species (but see Honěk et al ., , ). Our study shows a clear change in the ladybird community on lime trees over an 11‐year period in which H. axyridis invaded England, with an association between ladybird native status ( H. axyridis or native) and year (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are very few published long‐term studies of ladybird communities in Europe, and even fewer that have encompassed the early invasion phase of a non‐native species (but see Honěk et al ., , ). Our study shows a clear change in the ladybird community on lime trees over an 11‐year period in which H. axyridis invaded England, with an association between ladybird native status ( H. axyridis or native) and year (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study shows a marked change in the ladybird community on lime trees (but not on pine trees or nettles) following the arrival of H. axyridis , with a strong suggestion that significant declines in A. bipunctata were caused by the invasive species. We further illustrate the importance of long‐term sampling (Day & Tatman, ; Honěk et al ., ) so that changes in insect communities can properly be assessed over many years. As such, data will continue to be collected from the field sites reported here, to facilitate a study of even longer duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGP of H. axyridis was demonstrated by field data using molecular gut-content analysis [52]. Many factors can affect the coexistence of exotic vs. native species, including aphid availability [7], the co-presence of other exotic species [53] and the receiving environment [54]. However, a long-term study of coccinellid communities in Central Europe over 35 years, demonstrated that the compositions of the guilds communities remained essentially similar [54].…”
Section: Discussionmentioning
confidence: 99%
“…In order to know whether different coccinellid species show distinct patterns of dispersal between arable crops, we performed stable isotope analysis of carbon and nitrogen on C. septempunctata, Hippodamia variegata Goeze (Coleoptera: Coccinellidae) and Propylea quatuordecimpunctata L. (Coleoptera: Coccinellidae), which are known to be the three most common aphidophagous coccinellids species in arable crops in the NE of the Iberian Peninsula (Pons and Eizaguirre 2009) and other southern European regions (Iperti 1966;Honek et al 2014). The aim was to investigate their movement between alfalfa and maize when the cycles of the two crops overlap, at four periods during the growing season: (1) when maize was at its early vegetative stage, (2) just after alfalfa cutting, (3) when alfalfa regrew after cutting and (4) after maize harvesting or plant drying.…”
Section: Introductionmentioning
confidence: 99%